The study of Cu/Fe-doped Al-MCM-41 to degrade Rhodamine B - Shunyi Li (IWA Publishing, 2021)
Textile wastewater has been recognized as one of the most difficult to treat environmental problems. Aiming to acquire an excellent treatment effect that could meet the stringent discharge regulations, a series of Cu- and Fe-doped Al-MCM-41 heterogeneous Fenton catalysts with different metal contents (1.21–3.45 wt%) were successfully synthesized by co-precipitation method to degrade Rhodamine B. Their physicochemical properties were analysed by X-ray diffraction, X-ray photoelectron spectroscopy, Fourier transform infrared spectroscopy, nitrogen physisorption and scanning electron microscopy. The incorporation of metal did not alter MCM-41's mesostructure, but increasing the contents of metal would decrease the order of MCM-41s’ structure. The effects of temperature, pH, H2O2 dosage, dye concentration and the dosage of catalysts on Rhodamine B degradation were also investigated. It was found that M2 with 2.71 wt% of active metals performed best on Rhodamine B degradation. For the high concentration of Rhodamine B (400 mg/L), the decolorization efficiency could reach 96.0% using only 40 mM H2O2 within 50 min at 60 °C. Further adding 40 mM of H2O2, the chemical oxygen demand removal reached 75.1% after 100 min. M2 showed excellent stability and could be reused at least three times without any obvious deterioration in catalytic activity. M2 fitted well with the Freundlich isotherms and the first-order rate model. HIGHLIGHTS A series of Cu- and Fe-doped Al-MCM-41 heterogeneous catalysts were synthesized to degrade RhB.; The structure of MCM-41 was preserved.; Catalysts had efficient and stable treatment performance.; The adsorption model and the reaction kinetic model were further studied.; The conditions of the RhB degradation reaction were optimized.;